2019
DOI: 10.1007/s12253-019-00677-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Metabolic Shift can Decrease Therapy Resistance in Human High-Grade Glioma Cells

Abstract: The high-grade brain malignancy, glioblastoma multiforme (GBM), is one of the most aggressive tumours in central nervous system. The developing resistance against recent therapies and the recurrence rate of GBMs are extremely high. In spite several new ongoing trials, GBM therapies could not significantly increase the survival rate of the patients as significantly. The presence of inter-and intra-tumoral heterogeneity of GBMs arise the problem to find both the pre-existing potential resistant clones and the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Experimental studies of highly malignant tumours (e.g., gliomas and hepatocellular carcinomas) indicate that the antitumour effect of rapalogs is significantly enhanced by inhibitors of glycolysis or OXPHOS/mitochondrial biogenesis [ 14 , 39 ]. Additional approaches such as autophagy, lipid oxidation/synthesis or other OXPHOS inhibitors, combined with current targeted therapies, have been successfully tested in malignancies other than breast cancer [ 40 , 41 , 42 ]. The results of these studies coincide with the observations that metformin treatment lowers, whereas obesity and insulin resistance increase, the incidence of breast cancer [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies of highly malignant tumours (e.g., gliomas and hepatocellular carcinomas) indicate that the antitumour effect of rapalogs is significantly enhanced by inhibitors of glycolysis or OXPHOS/mitochondrial biogenesis [ 14 , 39 ]. Additional approaches such as autophagy, lipid oxidation/synthesis or other OXPHOS inhibitors, combined with current targeted therapies, have been successfully tested in malignancies other than breast cancer [ 40 , 41 , 42 ]. The results of these studies coincide with the observations that metformin treatment lowers, whereas obesity and insulin resistance increase, the incidence of breast cancer [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…DMSO (1%) was used as a vehicle and was added to control cells as required. Concentrations were determined and used based on previous experiments and publications [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several approaches have been applied to target metabolism in glioblastoma as well as other cancers [ 51 , 52 , 53 ]. Different studies showed that deletion/inhibition of LDHA combined with treatment with drugs such as tamoxifen, taxol, or use of drugs alone (oxamate, phenformin, gossypol, galloflavin) could impact tumorigenesis by affecting glucose uptake and increasing tumor apoptosis (reviewed in [ 51 , 52 , 53 ]). Gossypol, for instance, is well tolerated in clinical trials and has shown promise in recurrent malignant glioma trials [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gossypol, for instance, is well tolerated in clinical trials and has shown promise in recurrent malignant glioma trials [ 54 ]. Combinations of rapamycin with chemotherapy (temozolomide, doxycycline, etomoxir) were shown to be effective strategies in GBM [ 53 ]. However, the common problem with drugs is that they have limited cell penetration; therefore, relatively high doses are required to have any significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Based on certain studies, their combination with chemotherapy could be effective, but it could significantly enhance the effect of anti-angiogenic therapy (bevacizumab) without increasing the severity of side effects (e.g. in metastatic NSCLC) [105][106][107].…”
Section: Metabolic Therapymentioning
confidence: 99%